FAKTOR PELAYANAN KESEHATAN, DUKUNGAN KELUARGA DAN MASYARAKAT DENGAN UPAYA PENCEGAHAN KEJADIAN RABIES DI WILAYAH KERJA PUSKESMAS PANDAN KECAMATAN SUNGAI TEBELIAN KABUPATEN SINTANG - Elvi Juliansyah Jamari; Febrian Nurdin (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Rabies is a very dangerous zoonotic disease that can cause death in animals and humans infected with the rabies virus in animal saliva. Animals such as dogs, cats and monkeys that suffer from rabies. This study aims to determine the relationship of health services, family support, and the community with efforts to prevent the incidence of rabies. The quantitative research method is cross sectional design with a population of 24,038 people. The method of sampling is using simple random sampling of 194 respondents. The results showed no significant relationship between prevention efforts with health services p value 0.064> Î± (0.005), there was a significant relationship between family support p value 0.027 <Î± (0.05), there was no significant relationship with community support p value 0.100> Î± (0.05). The conclusion of this study is that every family member, parent and child has a role to give each other information to remind each other with each other in preventing transmission of rabies caused by rhabdovirus.